The added value of shear wave elastography when combined to conventional ultrasonography and fine-needle aspiration cytology in detection of malignant thyroid nodule - Ahmed Adel Abdallah; Maha Zaki Mahmoud; Mohamed Salah Hassouna; Khaled Elkaffas; Ahmad Mohamed Eltelety; Sameh M. Zamzam (The Egyptian Journal of Otolaryngology)
Abstract Background This study aims to evaluate the effectiveness of ultrasound criteria, TI-RADS score, and elastography in distinguishing benign thyroid nodules from malignant ones, as a substitute for invasive diagnostic procedures. Although the minority of thyroid nodules is malignant, invasive diagnostic procedures are often necessary. Methods In this prospective study, a total of 104 thyroid nodules were assessed using fine-needle aspiration cytology. The euthyroid state of the patients was ensured. Conventional ultrasound and shear wave elastography (SWE) were performed by a single experienced operator. Final postoperative histopathologic findings were compared to conventional ultrasound and elastography findings. Results SWE elasticity indices (EIs) were found to be significantly higher in malignant nodules than benign ones (p < 0.05). Combined results of both TI-RADS and SWE increased the sensitivity of detection of malignant nodules. Conclusion Combined SWE and TI-RADS could enhance the diagnostic accuracy in differentiating thyroid nodules by leveraging their complementary strengths.